(untitled) - Robb, J. D.; 1950- (New York, 2019)
"Lieutenant Eve Dallas must keep the predator from becoming the prey. Lady Justice's criminal crusade is escalating rapidly, and if Eve can't stop this vigilante, there's no telling how much blood may be spilled."--
Keywords: (Fictitious character); Fiction; Dallas, Eve; Policewomen; Fiction; New York (State); Serial murder investigation; Fiction; Suspense fiction; Mystery fiction; Thrillers (Fiction)